1983
DOI: 10.2131/jts.8.205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental pollutants on the mitochondrial and red cell membranes.

Abstract: Most environmental pollutants affect biological membranes more or less, resulting in an increase in permeability of mitochondrial and red cell membranes, which causes changes in potassium compartmentation, and also impairment of oxidative phosphorylation of mitochondria. Authors classified various environmental pollutants from the mode of action on biological membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Exposure to toxic chemicals can cause health problems by interacting with biomolecules, known as molecular initiating events, which can disrupt various downstream physiological processes. 120 Although small molecular chemicals, such as PAHs 121 and aromatic amines, 122 attack nucleotides, and others, e.g., halogenated benzene, 123 target cell membranes, proteins also play a role in mediating adverse effects of contaminants. 124 However, the current non-target screening method still focuses on PFAS-relevant compounds while the interactions between emerging chemicals and proteins are still not clear by the current methods.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to toxic chemicals can cause health problems by interacting with biomolecules, known as molecular initiating events, which can disrupt various downstream physiological processes. 120 Although small molecular chemicals, such as PAHs 121 and aromatic amines, 122 attack nucleotides, and others, e.g., halogenated benzene, 123 target cell membranes, proteins also play a role in mediating adverse effects of contaminants. 124 However, the current non-target screening method still focuses on PFAS-relevant compounds while the interactions between emerging chemicals and proteins are still not clear by the current methods.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic functions of mitochondria are linked to their membranes [6][7][8]. Measurement of the rate of oxygen disappearance from a mitochondrial suspension is a sensitive method to study how well the electron transport system and the ATP-synthetase complex work.…”
Section: Introductionmentioning
confidence: 99%
“…Shannon et al [5] suggested that in vitro measurements of respiration would be useful to study the toxic effects of a variety of environmental chemicals. The metabolic functions of mitochondria are linked to their membranes [6][7][8]. Measurement of the rate of oxygen disappearance from a mitochondrial suspension is a sensitive method to study how well the electron transport system and the ATP-synthetase complex work.…”
Section: Introductionmentioning
confidence: 99%